Programa de atención e intervención psicosocial con metapropósito de construcción de habilidades psicosociales para la vida desde la gestión del bienestar en las relaciones de vida de jóvenes vinculados a la casa universitaria Asociación Nuevo Futuro de Colombia - Alfonso Vanegas, Jennifer Dayanna (Universidad Antonio Nariño, 2021)
The life project is a long-term personal plan, it is the orientation and the meaning that a person gives to his existence, it is a tool that aims to support personal growth, identifying the goals that are desired to be achieved through the recognition of abilities with which each human being has. Therefore, with this work, it was proposed to promote psychosocial skills for life from the management of well-being in the life relationships of young people linked to the university house of the new future association in Colombia, through a program of psychosocial care and intervention. The participants were young university students who were linked to the ICBF from childhood and entered the university house through their grades and behavior, ranging from 18 to 25 years old, the main topics addressed were life project, emotional intelligence, taking decisions, freedom and responsibility, assertive communication. The main achievement was to generate reflection on self-realization to achieve the goals of the psychosocial system and thus strengthen his life project through different areas such as social, academic, work and coexistence within the university house, where it was made Participating in the psychosocial team and caregivers, it is pertinent to highlight that autonomy in decision-making and the great capacity of the system to self-manage its own change was evident.